Influence of bodyweight on prednisolone pharmacokinetics in dogs - Bonnie L. Purcell; Andrew P. Woodward; Michael G. Leeming; Julien Rodolphe Samuel Dandrieux (PLoS ONE, 2025)
Background Larger dogs may be at greater risk of prednisolone side effects, yet there is limited research about how bodyweight affects prednisolone pharmacokinetics in dogs. Hypothesis/objectives To describe the relationship between prednisolone dose, bodyweight, body surface area (BSA) and prednisolone area under the curve (AUC) in dogs receiving prednisolone for medical reasons. Animals 25 client owned dogs receiving prednisolone for medical reasons. Methods Observational population pharmacokinetic study. Liquid chromatography tandem mass spectrometry was used for plasma prednisolone quantification. Data analysis was conducted in a two-stage approach using non-compartmental modelling. A Bayesian non-linear regression model described the relationship between AUC over 8 hours ( A U C 8 h r , ng·min/mL), bodyweight and prednisolone dose. Results From the allometric scaling model of the form AUC 8h = A · BW B , the scaling exponent B was.83 (90% credible interval (CrI):.60–1.06) and the coefficient A was 22.8 (90% CrI: 11.8–43.4). This model suggests that equivalent exposure would be obtained using an intermediate strategy between BSA and bodyweight dosing, but the total evidence provided was relatively weak. Conclusions and clinical importance Evidence was obtained regarding the nonlinear relationship between prednisolone pharmacokinetics and bodyweight in dogs; however, this model is currently too imprecise for clinical dose determination.